Transformasi Pembelajaran Menulis Cerpen melalui Model DDD-E Berbantuan AI pada Siswa kelas XI SMA - Zairin, Azfa; D, Yusra; Priyanto, Priyanto (DIKBASTRA: Jurnal Pendidikan Bahasa dan Sastra, 2026)
The integration of Artificial Intelligence (AI) into education often raises concerns regarding the loss of students’ originality and creative agency, particularly in literature education. This study aims to analyze the transformation of students’ creative processes in writing short stories through the implementation of the DDD-E (Decide, Design, Develop, Evaluate) instructional design model assisted by AI (ChatGPT, Gemini, and Leonardo AI). Using Robert E. Stake’s Instrumental Case Study approach, this study involved 11th-grade students at Muaro Jambi State High School No. 11 as participants. Data were collected through participant observation, in-depth interviews with teachers and students, and document analysis of AI chat logs, storyboards, and digital storytelling products. The research findings indicate that the integration of AI within the DDD-E framework serves as effective cognitive scaffolding at three levels: technical, pedagogical, and psychological. Key findings reveal that AI does not replace human creativity but rather acts as a cognitive partner that accelerates the ideation phase and aids in narrative visualization without undermining originality. Students demonstrate critical digital literacy skills through the process of filtering vocabulary and adapting content based on local wisdom. This study makes a theoretical contribution to the development of the "Humanizing AI" model in literature education and offers practical implications for strengthening the Pancasila Student Profile within the Merdeka Curriculum.